2015
DOI: 10.1371/journal.pone.0136663
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin and Evolution of the Extant System of B Chromosomes in Oryzomyini Radiation (Rodentia, Sigmodontinae)

Abstract: Heterogeneous supernumerary chromosomes (Bs) are recognized in the oryzomyines Holochilus brasiliensis, Nectomys rattus, N. squamipes, Oligoryzomys flavescens and Sooretamys angouya, representing about 10% of all known B-containing rodent species. They provide an outstanding model for understanding the origin, evolution and diversity of Bs in a phylogenetic context. Therefore, whole chromosome-specific probes were generated from flow-sorted Holochilus brasiliensis (HBR) autosomes 11 and 25+26 and chromosomes X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…Differences were also described in Bs of Holochilus brasiliensis, Nectomys rattus Pelzeln, 1883, and Oligoryzomys flavescens (Waterhouse, 1837) (Silva and Yonenaga-Yassuda 2004). Recently, FISH with Holochilus brasiliensis probes of sex chromosomes (X and Y) and both supernumeraries (B1 and B2) were performed, revealing positive signal on sex chromosome of 12 Oryzomyini species and Bs of Holochilus brasiliensis, Nectomys rattus and N. squamipes (Ventura et al 2015). No signal was observed in Bs of Oligoryzomys flavescens and Sooretamys angouya (G. Fischer, 1814), though, corroborating that supernumeraries in this group may have had independent origins (Ventura et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Differences were also described in Bs of Holochilus brasiliensis, Nectomys rattus Pelzeln, 1883, and Oligoryzomys flavescens (Waterhouse, 1837) (Silva and Yonenaga-Yassuda 2004). Recently, FISH with Holochilus brasiliensis probes of sex chromosomes (X and Y) and both supernumeraries (B1 and B2) were performed, revealing positive signal on sex chromosome of 12 Oryzomyini species and Bs of Holochilus brasiliensis, Nectomys rattus and N. squamipes (Ventura et al 2015). No signal was observed in Bs of Oligoryzomys flavescens and Sooretamys angouya (G. Fischer, 1814), though, corroborating that supernumeraries in this group may have had independent origins (Ventura et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We estimate that the founder AMO population must have colo- nized the island at least 11,500 years ago due to the geological formation of most of the island that dates to the Holocene and Pleistocene [Possomai et al, 2010] coinciding with the last glacial maximum when the continental shelf was exposed by falling sea levels, permitting the dispersal of a wide range of organisms [Leite et al, 2016]. Ventura et al [2015] showed a shared heterochromatic region in Orizomyini rodents which occurs in both A and B chromosomes in the Orizomyini tribe and dates about 3-7 million years, giving evidence that the total differentiation of the B chromosome system in this tribe is not completed. Therefore, our findings suggest that the B chromosomes of this AMO population are older than the estimated colonization of the island and likely are the result of a founder effect, which could have culminated the high frequency in the population.…”
Section: Discussionmentioning
confidence: 99%
“…B chromosomes (Bs) appear as supernumerary elements to the standard chromosome complement and are highly variables (Silva and Yonenaga 2004; Vujošević and Blagojević 2004; Ventura et al 2015). The B of Akodon montensis studied here had identical morphology to those detected in Brazil (Yonenaga-Yassuda et al 1975; Kasahara and Yonenaga-Yassuda 1982; Yonenaga-Yassuda et al 1992; Fagundes et al 2000; Silva and Yonenaga-Yassuda 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the frequency of B chromosomes is common among populations (Silva and Yonenaga Yassuda 2004; Vujošević and Blagojević 2004; Ventura et al 2015). In Akodon montensis the frequency of individuals with Bs appears to vary among localities, but several populations were studied with low sample size.…”
Section: Discussionmentioning
confidence: 99%